2019
DOI: 10.1016/j.ynstr.2019.100160
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mild stress induces anhedonic behavior and changes in glutamate release, BDNF trafficking and dendrite morphology only in stress vulnerable rats. The rapid restorative action of ketamine

Abstract: Depression is a debilitating mental disease, characterized by persistent low mood and anhedonia. Stress represents a major environmental risk factor for depression; the complex interaction of stress with genetic factors results in different individual vulnerability or resilience to the disorder. Dysfunctions of the glutamate system have a primary role in depression. Clinical neuroimaging studies have consistently reported alterations in volume and connectivity of cortico-limbic areas, where glutamate neurons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 64 publications
7
93
2
Order By: Relevance
“…In rats vulnerable to chronic mild stress, ketamine was noted to result in reversal of anhedonic behavior, partial attenuation of hippocampal impairments in presynaptic release of glutamate and GABA, along with complete restoration of dendritic atrophy and dendritic BDNF mRNA trafficking. 108 In a mouse model of social defeat stress, ketamine was noted to attenuate reductions in BDNF, dendritic spine density, GluA1 and PSD-95 (both markers of synaptogenesis) in the PFC, dentate gyrus and CA3 region of the hippocampus at 8 days following drug administration. 109 In an investigation employing two-photon imaging in the PFC of living mice exposed to chronic stress, ketamine rescued elimination of postsynaptic dendritic spines and reversed the loss of coordinated activity of multicellular ensembles in projection neurons.…”
Section: Antidepressant Mechanisms Of Ketamine and Potential Biochemimentioning
confidence: 99%
“…In rats vulnerable to chronic mild stress, ketamine was noted to result in reversal of anhedonic behavior, partial attenuation of hippocampal impairments in presynaptic release of glutamate and GABA, along with complete restoration of dendritic atrophy and dendritic BDNF mRNA trafficking. 108 In a mouse model of social defeat stress, ketamine was noted to attenuate reductions in BDNF, dendritic spine density, GluA1 and PSD-95 (both markers of synaptogenesis) in the PFC, dentate gyrus and CA3 region of the hippocampus at 8 days following drug administration. 109 In an investigation employing two-photon imaging in the PFC of living mice exposed to chronic stress, ketamine rescued elimination of postsynaptic dendritic spines and reversed the loss of coordinated activity of multicellular ensembles in projection neurons.…”
Section: Antidepressant Mechanisms Of Ketamine and Potential Biochemimentioning
confidence: 99%
“…It has also been reported that the regulation of glutamate transporter 1 on astrocytes through the activation of TrkB is involved in the beneficial effects of ketamine on behavioral abnormalities and morphological changes in the hippocampus of chronic unpredictable mild stress (CUMS)-exposed rats 88 . A recent study showed that ketamine restores depression-like phenotypes in CUMS-exposed vulnerable rats by rescuing the dendritic trafficking of Bdnf mRNA 89 . In addition, the ketamine-induced regulation of TrkB is independent of HNK 90 .…”
Section: Bdnfmentioning
confidence: 99%
“…Brain‐derived neurotrophic factor (BDNF) is a member of the neurotrophin family, which plays a central role in neurogenesis, differentiation, survival, and synaptic plasticity (Leal, Bramham, & Duarte, 2017; Numakawa, Odaka, & Adachi, 2018; Tornese et al, 2019). BDNF is also an anorexigenic factor that regulates food intake, body weight, and metabolism.…”
Section: Introductionmentioning
confidence: 99%